2020
DOI: 10.3390/ijerph17228517
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Material Deprivation and Avoidable Mortality in Lisbon, Portugal

Abstract: There is considerable evidence pointing to the existence of a socioeconomic gradient in mortality, which tends to be steeper in urban areas. Similar to other European cities, Lisbon is far from homogeneous since considerable geographical inequalities exist between the more advantaged and the more deprived neighborhoods. The main goals of this study are to describe the geographical pattern of premature deaths (before 65 years old), avoidable deaths (preventable and amenable to healthcare) and cause-specific mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
1
6
0
1
Order By: Relevance
“…Other studies [34] have shown that the impact of deprivation on mortality in small areas is sustained over time, moreover, a significant statistical association is found between all the causes of death in that study and deprivation. In the deprived areas, the impact on mortality is sometimes attributed to their physical and social environments [35], but neighborhood disadvantage and economic stress also may impact individual mortality [36] independently from individual socioeconomic characteristics.…”
Section: Discussionsupporting
confidence: 59%
“…Other studies [34] have shown that the impact of deprivation on mortality in small areas is sustained over time, moreover, a significant statistical association is found between all the causes of death in that study and deprivation. In the deprived areas, the impact on mortality is sometimes attributed to their physical and social environments [35], but neighborhood disadvantage and economic stress also may impact individual mortality [36] independently from individual socioeconomic characteristics.…”
Section: Discussionsupporting
confidence: 59%
“…Each country is specific and this fact should be taken into account when formulating health policies. For instance, poverty is closely linked to treatable mortality ( 63 , 64 ) and in this context it should be borne in mind that if the health system provides health care to populations with higher poverty and other socio-economic specificities, it may be reflected also in a greater need for financial resources in the system ( 20 ). Treatable mortality should be interpreted both as an indicator of health care quality and as a reflection of the unequal distribution of socio-economic resources ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no universal definition of avoidable mortality in terms of age cut-off and diseases included. The Canadian Institute of Health Information (CIHI) has defined potentially avoidable mortality as “premature deaths that could potentially have been avoided through all levels of prevention (primary, secondary, tertiary)” [ 15 ], where premature death refers to the death that occurs before age 75 and the avoidable mortality component includes both preventable deaths and treatable deaths [ 16 , 17 ]. By way of illustration, vaccine-preventable diseases are included in the list due to their preventability whereas hypertensive diseases are included due to their treatability.…”
Section: Introductionmentioning
confidence: 99%
“…PPAM has been consistently reported to be associated with socioeconomic deprivation [ 10 , 16 , 18 ]. Furthermore, childhood adversity has been reported to be associated with family socioeconomic status in childhood and one’s socioeconomic status in adulthood [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%